Climate adaptation in a minor crop species: is the cocoa breeding network prepared for climate change?. Issue 7 (9th August 2018) - Farrell, Aidan D.; Rhiney, Kevon; Eitzinger, Anton; Umaharan, Pathmanathan
ABSTRACT: Plant breeding has undoubtedly been successful in increasing the yield of high value commodity crops. In recent decades, efforts have been made to repeat this success in 'orphan crops' through a network of regional and national organizations largely composed of public and not-for-profit institutions. Adapting to climate change is a key challenge for these networks. Here we seek to analyze the particular challenges that characterize efforts to develop climate-smart varieties in minor crops, using the example of cocoa. Cocoa is a high-value commodity with a global research network; however, to date it has not received sustained attention from major global research centers. We estimate that globally <100 new cocoa varieties have been released since 2000, and our analysis suggests that this low number is constrained not by a limited availability of germplasm, but by limitations in the infrastructure focused on the final stages of breeding. We conclude that selecting minor crops for a future climate requires a long-term, regional approach that exploits modern technologies, integrates participatory selection, and is managed through a centrally funded network.